Fluorescence from rubrene single crystals : interplay of singlet fission and energy trapping - Gurzadyan, Gagik G. (2014)
We have studied fluorescence in rubrene single crystals by use of fluorescence up-conversion, fluorescence anisotropy, and temperature-dependent time-resolved fluorescence techniques. Thermally activated singlet fission was demonstrated to play an important role in the quenching of two intrinsic fluorescence bands, 565 and 610 nm. At low temperatures, singlet fission is suppressed while another process, namely energy trapping, becomes pronounced. The 650 nm fluorescence originates from the hole trap states located 0.27 eV above the valence band.